The Contribution of Oxidative Stress to NF1-Altered Tumors - Elisabetta Kuhn; Federica Natacci; Massimo Corbo; Luigi Pisani; Stefano Ferrero; Gaetano Bulfamante; Donatella Gambini (MDPI AG, 2023)
The neurofibromatosis-1 gene (NF1) was initially characterized because its germline mutation is responsible for an inherited syndromic disease predisposing tumor development, in particular neurofibromas but also various malignancies. Recently, large-scale tumor sequencing efforts have demonstrated NF1 as one of the most frequently mutated genes in human cancer, being mutated in approximately 5-10% of all tumors, especially in malignant peripheral nerve sheath tumors and different skin tumors. NF1 acts as a tumor suppressor gene that encodes neurofibromin, a large protein that controls neoplastic transformation through several molecular mechanisms. On the other hand, neurofibromin loss due to NF1 biallelic inactivation induces tumorigenic hyperactivation of Ras and mTOR signaling pathways. Moreover, neurofibromin controls actin cytoskeleton structure and the metaphase-anaphase transition. Consequently, neurofibromin deficiency favors cell mobility and proliferation as well as chromosomal instability and aneuploidy, respectively. Growing evidence supports the role of oxidative stress in NF1-related tumorigenesis. Neurofibromin loss induces oxidative stress both directly and through Ras and mTOR signaling activation. Notably, innovative therapeutic approaches explore drug combinations that further increase reactive oxygen species to boost the oxidative unbalance of NF1-altered cancer cells. In our paper, we review NF1-related tumors and their pathogenesis, highlighting the twofold contribution of oxidative stress, both tumorigenic and therapeutic.